Endocrine fibroblast growth factors in domestic animals. - Brinker EJ; Hardcastle MR; Dittmer KE; Graff EC (Elsevier B.V., 2024)
Fibroblast growth factors (FGFs) are a group of structurally homologous yet functionally pleiotropic proteins. Canonical and intracellular FGFs have primarily autocrine or paracrine effects. However, the FGF19 subfamily, composed of FGF15/19, FGF21, and FGF23, act as endocrine hormones that regulate bile acid, metabolic, and phosphorus homeostasis, respectively. Current research in human and rodent models demonstrates the potential of these endocrine FGFs to target various diseases, including disorders of inherited hypophosphatemia, chronic liver disease, obesity, and insulin resistance. Many diseases targeted for therapeutic use in humans have pathophysiological overlaps in domestic animals. Despite the potential clinical and economic impact, little is known about endocrine FGFs and their signaling pathways in major domestic animal species compared with humans and laboratory animals. This review aims to describe the physiology of these endocrine FGFs, discuss their current therapeutic use, and summarize the contemporary literature regarding endocrine FGFs in domestic animals, focusing on potential future directions.
Keywords: Domestic animals; Endocrine FGFs; FGF19; FGF21; FGF23; Fibroblast growth factors